2020
DOI: 10.1108/qmr-12-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Corporate branding and value creation for initiating and managing relationships in B2B markets

Abstract: Purpose This study aims to fill a gap in branding literature concerning the effect of corporate brand relationships on brand value through the case study method in a business-to-business (B2B) context. The objectives of this study can be framed in the following three questions: what are the main constituents of a corporate brand; how does a corporate brand generate tangible and intangible brand value for their business customers; and how do tangible and intangible brand benefits influence relationship initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 139 publications
(172 reference statements)
1
10
0
Order By: Relevance
“…Superior brand image translates to increased brand value which influences buyers' willingness to pay a premium price. Companies may gain from premium pricing by building a strong brand due to the price-inelastic nature of corporate buying (Ozdemir et al, 2020).…”
Section: Enterprise Brand Orientation and Brand Performancementioning
confidence: 99%
“…Superior brand image translates to increased brand value which influences buyers' willingness to pay a premium price. Companies may gain from premium pricing by building a strong brand due to the price-inelastic nature of corporate buying (Ozdemir et al, 2020).…”
Section: Enterprise Brand Orientation and Brand Performancementioning
confidence: 99%
“…Companies may set consumer expectations by communicating the value commitments of their corporate brands in a branding framework (Ozdemir et al, 2020).While brand trust is significant for customers to trust risky products developed by a brand, it is also significant to create the right values in order to gain customers' trust. Chesbrough et al, (2018a) revealed that "in the highly competitive hotel industry markets, companies need to continually invest in the creation of new value.…”
Section: Hyphotesismentioning
confidence: 99%
“…The review is based on “Corporate branding and value creation for initiating and managing relationships in B2B markets” by Ozdemir et al (2020), published in Qualitative Market Research.…”
Section: Commentmentioning
confidence: 99%